2009
DOI: 10.1197/jamia.m3000
|View full text |Cite
|
Sign up to set email alerts
|

Describing and Modeling Workflow and Information Flow in Chronic Disease Care

Abstract: In response to the analysis of workflow and information flow, the authors developed ten guidelines for design of HIT to support chronic disease care, including recommendations to pursue modular approaches to design that would support disease-specific needs. The study demonstrates the importance of evaluating workflow and information flow in HIT design and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 39 publications
2
86
0
Order By: Relevance
“…Workflow diagrams have been used to optimize population health management systems 13,14 Unertl and colleagues modeled workflow, information flow, and work practices in side-by-side diagrams representing chronic disease care; they found that clinic staff will create inefficient "work-arounds" to accomplish tasks when the technology does not fit their needs. 15 …”
Section: Workflows To Describe Data Contextmentioning
confidence: 99%
“…Workflow diagrams have been used to optimize population health management systems 13,14 Unertl and colleagues modeled workflow, information flow, and work practices in side-by-side diagrams representing chronic disease care; they found that clinic staff will create inefficient "work-arounds" to accomplish tasks when the technology does not fit their needs. 15 …”
Section: Workflows To Describe Data Contextmentioning
confidence: 99%
“…Modelling workflow and information flow is an established methodology for studying medical scenarios, such as chronic patient care (Unertl et al, 2009). This approach is based on the soft systems methodology (Checkland, 2000;Mingers, 2000) which is well documented as a methodology for process innovation (Presley, Sarkis, & Liles, 2000).…”
Section: Design and Flow Of Emergency Response Participationmentioning
confidence: 99%
“…The information system, which integrates patient, physician and EMS participation, advanced matching of prescription medication, and location-based social networking, is being initially focused on anaphylaxis with broad potential for other chronic conditions. The ERC system and anaphylaxis app design emerged by following a soft systems methodology (Checkland, 2000) of modelling workflow and information flow (Durugbo, Tiwari, & Alcock, 2013;Hibberd & Evatt, 2004;Unertl, Weinger, Johnson, & Lorenzi, 2009). To facilitate this process we engaged with a pool of 18 medical professionals across the fields of Emergency Medicine (8), Allergy and Clinical Immunology (4), Pharmacology (4) and Public Health (4).…”
Section: Introductionmentioning
confidence: 99%
“…To study performance in the process of information exchange, some authors recommend studying the work processes and communication activities associated with information and communication practices (Georgiou, Marks, Braithwaite, & Westbrook, 2013;Unertl, Weinger, Johnson, & Lorenzi, 2009). Work processes or workflow factors include sequences of routine activities and tasks, relationships among activities, roles, and responsibilities and are influenced by internal or external factors (Unertl, Johnson, & Lorenzi, 2012;Unertl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Work processes or workflow factors include sequences of routine activities and tasks, relationships among activities, roles, and responsibilities and are influenced by internal or external factors (Unertl, Johnson, & Lorenzi, 2012;Unertl et al, 2009). Communication activities or information flow incorporate the transfer of information between individual actors (e.g., registered nurses (RNs) or other healthcare providers) (Unertl et al, 2009). From our perspective, Alter's (2013) work system framework (WSF) is an option for studying workflow and information flow-related aspects of health information-exchange activities in a healthcare setting.…”
Section: Introductionmentioning
confidence: 99%